INTERNATIONAL COMMUNICATION IN AN EFFORTS TO IMPROVE ISLAMIC PREACHING WITH A GLOBAL PERSPECTIVE - Salsabila, Fahmi (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
In the era of globalization, Islamic preaching (da’wah) has transcended local boundaries, reaching diverse global audiences. The role of international communication is pivotal in enabling the effective dissemination of Islamic teachings across cultures and nations. This study examines the strategic use of international communication in enhancing Islamic da’wah, with a particular focus on digital media, language proficiency, and cultural awareness. A descriptive qualitative approach, utilizing a literature review, highlights that the integration of digital platforms, mastery of international languages, and sensitivity to cultural differences are key factors in the success of global preaching. Furthermore, with the right communication strategies, Islamic teachings can be shared more effectively, fostering a peaceful and inclusive global understanding of Islam. This research underscores the necessity for preachers and Islamic institutions to enhance their international communication capabilities to ensure that Islam's message resonates positively with the global community.